2016
DOI: 10.1200/jco.2016.67.4846
|View full text |Cite
|
Sign up to set email alerts
|

Obesity As a Risk Factor for Anthracyclines and Trastuzumab Cardiotoxicity in Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: International audiencePurposePatients with metabolic syndrome have a greater risk of cardiovascular disease, although their susceptibility to chemotherapy-induced cardiac disease is not well documented. The aim of this meta-analysis was to assess associations between obesity or being overweight and cardiotoxicity from anthracyclines and sequential anthracyclines and trastuzumab in patients with breast cancer.MethodsWe performed a random-effects analysis and a network meta-analysis and assessed publication bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 67 publications
6
101
1
5
Order By: Relevance
“…In addition, the selected nature of our cohort, which included very few women with BMI >35kg/m 2 , may have biased against a signal. Nonetheless, the relationship between body morphology and composition with anthracycline/Trastuzumab cardiotoxicity has become a matter of increasing interest, with a detailed systematic review and meta-analysis being only recently published [27]. In keeping with our findings, this concludes that ‘overweight and obesity are risk factors for cardiotoxicity from anthracyclines and sequential anthracyclines and trastuzumab’.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the selected nature of our cohort, which included very few women with BMI >35kg/m 2 , may have biased against a signal. Nonetheless, the relationship between body morphology and composition with anthracycline/Trastuzumab cardiotoxicity has become a matter of increasing interest, with a detailed systematic review and meta-analysis being only recently published [27]. In keeping with our findings, this concludes that ‘overweight and obesity are risk factors for cardiotoxicity from anthracyclines and sequential anthracyclines and trastuzumab’.…”
Section: Discussionsupporting
confidence: 84%
“…In keeping with our findings, this concludes that ‘overweight and obesity are risk factors for cardiotoxicity from anthracyclines and sequential anthracyclines and trastuzumab’. Such associations are postulated to be driven in part by reduced levels of the adipocytokine (adipocyte-derived hormone) adiponectin in obese patients: adiponectin-knockout mice appear more susceptible to doxorubicin-induced cardiac contractile dysfunction, whilst exogenously-administered adiponectin protects such mice, and enhances cardiac function in wild-type mice treated with doxorubicin (reviewed in [27]).…”
Section: Discussionmentioning
confidence: 99%
“…Higher body mass index has also been shown to significantly increase the odds of cardiac dysfunction associated with anthracycline or sequential treatment with anthracycline and trastuzumab. In a meta‐analysis of 15 studies, a body mass index >25 or >30 kg/m 2 was associated with 1.32 (95% CI, 1.06–1.80) and 1.47 (95% CI, 0.95–2.28) times the odds of cardiotoxicity compared with a normal body mass index 58. Cardiac risk scores have been developed to predict the risk of cardiotoxicity associated with trastuzumab, including several risk factors such as age, hypertension, diabetes mellitus, coronary artery disease, atrial fibrillation or flutter, renal dysfunction, and use of adjuvant chemotherapy 11, 57.…”
Section: Risk Factors For Cardiotoxicity Associated With Her2 Targetementioning
confidence: 99%
“…Of note, circulating HER2 is derived from the extracellular domain, which can be measured after its release in the blood stream. On the other hand, studies have indicated that obesity might increase the risk of cardiac toxicity in breast cancer patients who received trastuzumab (HER2-targeted monoclonal antibody) therapy [108], [109], [110]. Evidence shows that HER2 plays important physiological roles in the development of the heart and cardiomyocyte survival [111], [112].…”
Section: Characteristics Of Her2 Expressionmentioning
confidence: 99%